Transcriptomic and physiological analyses reveal that cytokinin is involved in the compound leaf development of alfalfa - Mei, Hongyao; Yan, Jiajun; Jia, Xuexin; Wang, Weilin; Li, Shuangshuang; Sun, Ruiqi; Jiang, Hongjiao; Xie, Lijun; Zhou, Chuanen; Bai, Shiqie; Han, Lu (Frontiers in Plant Science, 2025)
Alfalfa is one of the primary forages, and its yield is largely dependent on the development of its leaf. In this study, to elucidate the mechanism of compound leaf development, we isolated and examined the alfalfa phenotype Chuancao No.7, exhibiting five leaflets. The agronomic traits of the Chuancao No.7 including the leaf blade area, leaf/stem ratio, total fresh weight, and dry weight showed significant increases compared to those of the wild-type. Analyses of forage quality traits indicated significant differences in crude protein (CP), acid detergent fiber (ADF), crude fat (CF), water-soluble sugars (WSS), carbon content, ash composition content, and phosphorus content between Chuancao No.7 alfalfa and wild-type. Transcriptomic profile analysis revealed that differentially expressed genes were identified in the cytokinin (CK) signaling pathway. Both exogenous treatment and endogenous CK content detection indicated that cytokinin played a key role in the development of the alfalfa compound leaf. These results serve as a valuable resource for optimizing the forage quality and exploring the excellent germplasm of alfalfa.